2018
DOI: 10.1002/ar.24039
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variation in Maxillary Sinus Ostium Positioning: Implications for Nasal‐Sinus Disease

Abstract: Among humans, superiorly located maxillary sinus ostia (MSO) result in drainage complications and maxillary sinus (MS) disease. While previous studies investigate maxillary sinusitis frequency or MSO‐position relative to specific nasal landmarks, few explore MSO‐position to overall MS dimensions. This study investigates whether MSO‐position relates to MS size/shape and if sex‐based differences exist. Twenty‐nine landmarks, placed on magnetic resonance images (MRIs) of 109 individuals (males = 57; females = 52)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 67 publications
4
23
0
Order By: Relevance
“…This finding corroborates the findings of the study of Aktuna Belgin et al; Özdemir et al and Butaric et al stated that maxillary sinus development continues into the second and third decade of life in females and males, respectively, with an age-associated decrease in volume occurring after development is completed. All these results have been confirmed by Rani et al [ 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…This finding corroborates the findings of the study of Aktuna Belgin et al; Özdemir et al and Butaric et al stated that maxillary sinus development continues into the second and third decade of life in females and males, respectively, with an age-associated decrease in volume occurring after development is completed. All these results have been confirmed by Rani et al [ 55 , 56 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…The location of the AMO was determined by some of the studies and case reports based on the landmarks on the lateral nasal wall, such as the anterior and posterior fontanelle [ 1 , 10 , 31 – 33 ]. Other studies have identified the location of the ostium based on their distance from the landmarks such as floor of the sinus and anterior wall of the sinus [ 9 , 34 , 35 ]. Due to the variability of landmarks on the lateral nasal wall, we chose the latter approach based on measurements [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vertical and antero-posterior measurements for the location of AMO was determined by using the technique suggested by Butaric et al [ 9 ]. The distance of the AMO from the floor of the sinus (C) was calculated using the coronal CBCT sections, by measuring the distance between 2 horizontal lines A1-A (passing through the most inferior point of the AMO) and B1-B (passing through the most inferior point on the floor of the maxillary sinus) Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The location of the AMO was determined by some of the studies and case reports based on the landmarks on the lateral nasal wall, such as the anterior and posterior fontanelle [1,9,32,33,34] Other studies have identi ed the location of the ostium based on their distance from the landmarks such as oor of the sinus and anterior wall of the sinus. [35,36,37] Due to the variability of landmarks on the lateral nasal wall, we chose the latter approach based on measurements. [38,39] In our study the height of the AMO from the oor of the sinus was 19.93 ± 1.68 mm.…”
Section: Discussionmentioning
confidence: 99%